Service excellence for sustainability : lessons from Malaysia, Japan, and Taiwan - Elias, Nur Fazidah; Jenal, Ruzzakiah; Mohd Amin, Hazilah; Mohamed, Hazura; Hanawi, Siti Aishah; Service Science Symposium 2019 : Malaysia) (Singapore : Springer, 2021)
This book provides significant conceptual and empirical contributions to the understanding of service science and the practices of service sectors in the wake of the fourth industrial revolution bringing together a collection of articles written by keynote and invited speakers at the 2nd Service Science Symposium held on 24 November 2019. The symposium was organised by the Serviceology Society Malaysia (SESMA), which aims to bring service researchers and practitioners under one roof to redefine service concepts and ideas and explore their application in real industrial and community settings. In their contributions, authors present multiple real-world cases of service systems to demonstrate how organisations can incorporate service science to achieve sustainable development. By re-examining the existing service science models and the value creation process using valuable insights obtained from industries and communities in Malaysia, Japan and Taiwan, the authors present a new way forward for organisations.
Contents -- Preface -- List of Abbreviations -- List of Figures -- List of Tables -- Preface -- Chapter I: Introduction to Service Science -- Chapter II: Service Science And Sustainability -- Chapter III: Service sustainability paradigm as a basis for transformative service society -- Chapter IV: Inland Port in Malaysia: Logistical Revisit -- Chapter V: Think Global, Act Local: Strategies to Develop a Sustainable Mobility Program in Promoting Socioeconomic Development for a Better Quality Education,- Chapter VI: Media Psychology in New Era Communication -- Chapter VII: Critical Success Factors for Adopting Servitization Strategy -- Reference -- List of authors (author brief) -- Index.
Includes index.
Keywords: Service industries -- Congresses; Sustainable development -- Congresses